Danerne og det danske kongeriges opkomst – Om forskningsprogrammet »Fra Stamme til Stat i Danmark« - Näsman, Ulf (Kuml, 2006)
The Danes and the Origin of the Danish Kingdom On the Research Programme “From Tribe to State in Denmark” Since the 1970’s, the ethnogenesis of the Danes and the origin of the Danish kingdom have attracted increased interest among Danish archaeologists. Marked changes over time observed in a growing source material form a new basis of interpretation. In written sources, the Danish realm does not appear until the Viking Age. The formation of the kingdom is traditionally placed as late as the 10th century (Jelling and all that). But prehistorians have raised the question whether the formation of the kingdom was not a much longer course. Some scholars believe that we have to study the periods preceding the Viking Age to be able to understand the development, at least from the 3rd century. In Scandinavia, this covers the Late Roman Iron Age, the Migration and Merovingian periods, as well as the early Viking Age. In a Continental perspective, it parallels the Late Antiquity (3rd-6th centuries) and the Early Middle Ages (6th-10th centuries). In 1984, the Danish Research Council launched the research programme “From Tribe to State in Denmark” which aimed to understand the formation of the Danish kingdom by studying the interaction between economic, social, and political circumstances from the Roman Period to the Viking Age. This paper presents a short synthesis of my work in the programme. Two themes have been brought into focus: 1) The ethnogenesis of the Nordic peoples: the formation of the tribes that appear in the few and problematic written sources of the first millennium AD, in casu the Danes; 2) The making of the Nordic kingdoms: in this case Denmark. A problem with this kind of long-term research is the inherent teleological perspective, revealed in the programme title. It is essential for me to emphasise that the early Danish kingdom was not a self-evident formation but the result of a series of concrete historical circumstances. There have been alternative possibilities at several occasions. In Scandinavia, the period is prehistoric. However, in South Scandinavia it deserves to be labelled protohistoric. Scandinavian archaeologists often forget or ignore the fact that in large parts of Europe, the first millennium AD is a historical period. The Scandinavian development is too often evaluated in isolation from the rest of Europe, in spite of the fact that the material culture demonstrates that interaction with continental as well as insular powers was continuously influencing Scandinavia. Necessarily, a relevant approach to Scandinavian late prehistory includes a historical dimension and a European perspective. South Scandinavian societies were over time linked to different realms in Europe. The Danish development was certainly part of a common west European trajectory. The best possibility of interpreting the archaeological record of South Scandinavia is by analogy with historians’ interpretations of other more or less contemporary Germanic peoples, based on descriptions in the written sources. Long-term studies of Scandinavian societies in the first millennium AD has laid new ground on which scholars have to build their image of the making of a Danish kingdom. The paper briefly describes some of the results and focuses on changes in the material that I find significant. Rural settlement: Great progress in the study of Iron Age and Early Mediaeval farming suggests economic growth, a development from subsistence economy to a production of a surplus, from collective forms of farming to individually run farmsteads, from small family farmsteads to large farms and manors. It is the surplus created by this expansion that could carry the late Viking and high medieval Danish kingdom with its administration, military power, church, towns, etc. Trade and exchange: Prestige-goods exchange dominated in the beginning of the period. Goods came from various parts of Europe. The connections to central and east Europe were broken in the sixth century, not to be reopened until the Viking Age. This explains the dominating position held by West European material culture in the development of South Scandinavia. Thus, South Scandinavia became part of the commercial zone of West Europe, certainly an important element in the making of the Danish kingdom. In the Viking Age, the rapid urbanisation demonstrates that Denmark gained great profit from its key position in the North Sea-Baltic trade network. Central places and early towns: Complex settlements appeared already in the Late Roman Iron Age, e.g. Gudme/Lundeborg, Funen. Further central sites appeared, and the number of central places grew rapidly. By the year 700, they are found in virtually every settlement area of South Scandinavia. The sites were not simple trading stations, as most were labelled a few years ago, but many also fulfilled important political, social, and religious functions; some were also manorial residences. The resident elite based their power on the mobilisation of the rural surplus; at the same time, one can say that the stimulus to produce a rural surplus was probably caused by an increasing demand from the elite at the centres. In the Viking Age, urbanisation began, which meant that the old central places lost their position and were replaced by towns like Hedeby, Ribe, and Århus. Excavations show that urbanisation started in the 8th century, a little later than the famous emporia Quentovic, Dorestad, Hamwic, and Ipswic. So today, it must be concluded that at the threshold to the Viking Age, South Scandinavian societies had a more advanced economic system and a more complex social organisation than believed only 20 years ago. Warfare: The dated indications of war cluster in two periods, the 3rd to 5th centuries, and the 10th to 11th centuries. The early period could be characterised as one of tribal warfare, in which many polities were forced to join larger confederations through the pressure of endemic warfare and conquests. In the archaeological record, indicators of war seem to disappear after AD 500, not to reappear in large numbers until the Viking Age. Was this period a Pax Danorum? Indeed, the silent archaeological record could indicate that the Danes had won hegemony in South Scandinavia. This phase can be understood as a period of consolidation between an early phase of tribal warfare and a later phase in which the territorial defence of a Danish kingdom becomes visible in the record. Wars with the Carolingian empire in the 9th century are the first wars in Denmark to be mentioned in the written record. However, archaeology demonstrates the presence of serious military threats in the centuries before, e.g. the first dykes at Danevirke. The strategic localisation of the period’s defence works reveals that threats were met with both navy and army. According to the texts, the 9th century wars are clearly national wars, either wars of conquest on a large scale between kingdoms, or civil wars, which for a large part seem to be triggered by an aggressive Frankish diplomacy. The two phases of warfare mirror two different military political situations: in the Late Roman and Migration Periods they are tribal wars and conflicts over resource control; in the Late Merovingian Period and the Viking Age they concern a Danish kingdom’s territorial defence. Religious changes: The conversion is often considered a major turning point in Scandinavian history; and in a way it was, of course. But the importance of Christianisation is heavily overestimated. The conversion was simply a step in a process that started long before. The paganism of the Scandinavians must not mislead us into believing that they were barbarians. A great change in cult practice took place around AD 500 when the use of bogs and lakes for offerings rapidly decreased. Instead, religious objects are found hoarded in settlement contexts, sometimes in the great halls of the magnates. This indicates that the elite had taken control of religion in a new way. The close link between cult and elite continued uninterrupted after Christianisation; churches were built by the magnates and on their ground. Therefore, we have a kind of cult-site continuity. From the Migration Period, the archaeological material demonstrates a close link between cult and magnates. This is certainly one important element in the formation of a Danish kingdom. Political development: Analyses of material culture reveal that South Scandinavia in the Early Iron Age consisted of many small regions, and based on sources like Tacitus and Ptolemy, one can guess that they correspond to tribal areas. In the Late Roman Iron Age and the Migration Period, the formation of a South Scandinavian super-region can be discerned, but still subdivided into a small number of distinguishable culture zones, and, again, on the basis of written sources (Jordanes and Procopius), one can guess that small tribes had joined into larger confederations precisely as on the Continent. In my opinion, a Danish kingdom appeared not later than the sixth century. Based on the well-studied material culture of the early Merovingian Period, one can assume that it had its core area in Central Denmark - South Jutland, Funen, and Zealand – with a close periphery of North Jutland, South Halland, Scania, Blekinge, and Bornholm. Probably more loosely attached to the Danish hegemony was a more distant periphery in South Sweden. So the Danish kingdom already had a history when it first appeared in the Frankish sources at the end of the 8th century. Danish involvement in European politics is first clearly observable in 777 and again in 782. Obviously, the Danish kingdom was a political and military actor on the North European scene long before the Viking Age. In the light of all these arguments, three phases can be described: – Roman Iron Age: Tribal societies with chieftains or small kings. – Late Roman Iron Age, Migration Period, and early Merovingian Period: A process of amalgamation started and warfare characterises the period. The result is the formation of tribal confederations. Written sources speak in favour of the Danes as the people who eventually won hegemony over South Scandinavia. – Late Merovingian Period and Viking Age: A process began in which royal agents replaced local chieftains. The last area to be integrated under direct Danish royal rule, in the reign of Sven Forkbeard, was probably Scania. Thus Medieval Denmark appeared. Final remarks: As a result of archaeological achievements in the last decades, a number of traditional views about Scandinavian late prehistory appear less likely, or rather erroneous. It is an underestimation that the pagans were unable of organisation and that a formation of a Danish kingdom is unthinkable before the late Viking Age. Unfortunately, the ethnogenesis of the Danes is beyond the reach of study, but a rough hypothesis may be formulated. The Danes were once one of several tribes somewhere in South Scandinavia. Events outside the Scandinavian scene were of fundamental importance for the possibility of the Danish gens to grow in power in the Late Roman and Migration Periods. Already before the Merovingian Period, the Danes won hegemony between the Baltic and the North Sea. A Danish kingdom could probably be based on this key position. Its survival was by no means a matter of course. In their continued efforts to secure the Danish position, capable kings established the borders of high medieval Denmark in the course of the Viking Age. Ulf Näsman Institutionen för humaniora och samhällsvetenskap Högskolan i Kalmar